2020
DOI: 10.1155/2020/9373942
|View full text |Cite
|
Sign up to set email alerts
|

Applying Queuing Theory and Mixed Integer Programming to Blood Center Nursing Schedules of a Large Hospital in China

Abstract: Blood centers in large hospitals in China are facing serious problems, including complex patient queues and inflexible nursing schedules. This study is aimed at developing a flexible scheduling method for blood center nurses. By systematically analyzing the constraints that affect scheduling, a flexible scheduling model is established based on queuing theory and mixed integer programming. This combined model can reasonably determine the number of nurses required during a given working period and flexib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…(2020), who study the applying queuing theory and mixed integer programming in a large hospital in China, they considered an important outpatient services, has been unable to satisfy the increasing demand since the increasing number of patients, that resulting in long queues and affects patient satisfaction. Also, the data revealed that positive patient satisfaction by applying queuing theory and mixed nursing integer programming [11].…”
Section: Variablesmentioning
confidence: 97%
“…(2020), who study the applying queuing theory and mixed integer programming in a large hospital in China, they considered an important outpatient services, has been unable to satisfy the increasing demand since the increasing number of patients, that resulting in long queues and affects patient satisfaction. Also, the data revealed that positive patient satisfaction by applying queuing theory and mixed nursing integer programming [11].…”
Section: Variablesmentioning
confidence: 97%
“…Their proposed algorithm obtains better objective function values. Similarly, Luo et al [57] apply a two-stage approach: The first stage calculates the number of staff via a queuing model. The second stage designs schedules using the number of staff determined in stage one via a mixed integer program.…”
Section: Literature Reviewmentioning
confidence: 99%